Tubular structures : Sixth International Symposium on Tubular Structures, Melbourne, Australia, 1994 proceedings, Melbourne, Australia /: Sixth International Symposium on Tubular Structures, Melbourne, Australia, 1994 proceedings, Melbourne, Australia. (2021) - Unknown
No abstract available